Correlates of Agreement between Accelerometry and Self-reported Physical Activity - Cerin, Ester; Cain, Kelli L; Oyeyemi, Adewale L; Owen, Neville; Conway, Terry L; Cochrane, Tom; VAN Dyck, Delfien; Schipperijn, Jasper; Mitáš, Josef; Toftager, Mette; Aguinaga-Ontoso, Ines; Sallis, James F (Medicine and science in sports and exercise, 2016)
PURPOSE: Understanding factors that influence accurate assessment of physical activity (PA) and sedentary behavior (SB) is important to measurement development, epidemiologic studies, and interventions. This study examined agreement between self-reported (International Physical Activity Questionnaire-Long Form [IPAQ-LF]) and accelerometry-based estimates of PA and SB across six countries and identified correlates of between-method agreement. METHODS: Self-report and objective (accelerometry-based) PA and SB data were collected in 2002-2011 from 3865 adult participants in eight cities from six countries (Belgium, Czech Republic, Denmark, Spain, United Kingdom, and United States). Between-method relative agreement (correlation) and absolute disagreement (mean difference between conceptually and intensity-matched IPAQ-LF and accelerometry-based PA and SB variables) were estimated. Also, sociodemographic characteristics and PA patterns were examined as correlates of between-method agreement. RESULTS: Observed relative agreement (relationships of IPAQ-LF with accelerometry-based PA and SB variables) was small to moderate (r = 0.05-0.37) and was moderated by sociodemographic (age, sex, weight status, and education) and behavioral (PA-type) factors. The absolute disagreement was large, with participants self-reporting higher PA intensity and total time in moderate-to-vigorous-intensity PA than accelerometry. Also, self-reported sitting time was lower than accelerometry-based sedentary behavior. After adjusting for sociodemographic and behavioral factors, the absolute disagreement between pairs of IPAQ-LF and accelerometry-based PA variables remained significantly different across cities/countries. CONCLUSIONS: Present findings suggest systematic cultural and/or linguistic and sociodemographic differences in absolute agreement between the IPAQ-LF and the accelerometry-based PA and SB variables. These results have implications for the interpretation of international PA and SB data and correlate/determinant studies. They call for further efforts to improve such measures.
Keywords: Educational Status; Accelerometry; Sedentary Behavior; Female; stupeň vzdělání; akcelerometrie; Age Factors; ženské pohlaví; sedavý životní styl; volnočasové aktivity; věkové faktory; lidé; Self Report; cvičení; Leisure Activities; Sex Factors; tělesná hmotnost; Male; sexuální faktory; Body Weight; mužské pohlaví; zpráva o sobě; Exercise; Humans